Educational Cost and Efficiency of Public Secondary Schools in Ondo State, Nigeria - Aina Moyinoluwa , Adejuwon; Temiloluwa Mabel , kinde; ngba-Akoko , k u (International Journal of Educational Management, 2025)
Educational cost is a key factor that determines the level of efficiency in public secondary schools. This study therefore examined the relationship between educational cost and efficiency of public secondary schools in Ondo state, Nigeria. T he descriptive research design of the survey type and ex- post-facto design wer adopted for the study. Multi-stage sampling techniques was used to select the 45 schools involved in the investigation. The respondents comprised of 45 principals and 450 students. Two self-developed instruments titled "Proforma of Educational Cost and Efficiency of Public Secondary Schools" (PECEPSS), and "Educational Cost and Efficiency of Public Secondary Schools" (ECEPSS) were used to collect data. Three research questions were answered and two hypotheses were tested. Percentage, mean, and standard deviation were employed to answer he research questions, while Pearson product moment correlation statistics(PPMC) was used to test the hypotheses at 0.05 level of significance. Findings from the study revealed that, there was a negative relationship between educational cost and efficiency [ r(424)= 0.434, p < 0.05]. Also, negative relationship occurs between private cost and efficiency [r(424)= -0.169, p < 0.05] It was concluded that as the private cost increases there was also an increase in the efficiency level in public secondary schools in Ondo state. Based on the findings, it was recommended that Government should pay more attention on funding public secondary schools. Also, parents should be encouraged to improve on spending on their children so as to improve the students’ academic performance.